Peningkatan kemampuan numerasi mahasiswa melalui pembelajaran e-modul statistika terintegrasi flipbook dan augmented reality - Santia, Ika; Darsono, Darsono; Handayani, Aprilia Dwi; Nurfahrudianto, Aan; Puspitoningrum, Encil (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2023)
Abstract: This research was motivated by the low numeracy of students in statistics courses, which contradicts the importance of numeracy. For this reason, an integrated statistics e-module with a flipbook and augmented reality was developed with the aim that, through learning using this e-module, it can improve student numeracy. The use of flipbooks and augmented reality programs as an effort to integrate knowledge, pedagogy, and technology in an effort to improve numeracy. This research used quantitative methods, with the subjects being 58 students in statistics courses. The paired two-sample t-test technique was used to analyze the increase in numeracy through e-module learning. The data were analyzed with the help of the SPSS 21 for Windows program. The research results showed that there was an increase in student numeracy after using the e-module, with a significance value of 0.00 < 5% with t = -5.23> -t0.05, so learning using the statistics e-module integrated with flipbooks and augmented reality can improve student numeracy. Keywords: Numeracy; Integrated E-module, Statistic.